A multi-skeleton modelling approach based on top-down design and modular product design for development of complex product layouts. Issue 10 (2nd October 2016) - Chu, Dexin; Chu, Xuening; Li, Yupeng; Lyu, Guolin; Xue, Deyi
ABSTRACT: Top-down design (TDD) and modular product design (MPD) are two popular design strategies for development of complex products. Although integration of these two design strategies can improve the quality and efficiency for the development of complex products, it is difficult to implement the TDD and MPD strategies simultaneously due to the lack of tools that can handle modelling of the inheritance mechanism from the abstract design descriptions to the detailed design descriptions within TDD and modelling of the relatively independent design descriptions as groups within MPD. A new multi-skeleton modelling approach is introduced in this research for layout design of complex products based on TDD and MPD. First, through studies on the inheritance mechanism between design descriptions on different levels in the hierarchical product modelling architecture and the interface relationships between different modules, design information is classified into five categories: locations, interface features, design spaces, key features and kinematic constraints. Second, these different types of design information are modelled using three types of skeletons: location skeletons, interface skeletons and published skeletons. Third, a multi-skeleton modelling scheme is introduced for the development of product descriptions from relative abstract levels to more detailed levels recursively in TDD manner with relatively independent modules. This multi-skeleton modelling approach can be used to propagate changes of product descriptions on different levels, to improve design efficiency by reusing and modifying the existing modules, and to evaluate the design at early design stage without detailed design descriptions. In addition, the multi-skeleton model can be implemented in most CAD systems. A case study is used to illustrate the effectiveness of the new multi-skeleton modelling approach.